Days of Labour: Topographies of Power in Modern Peripheral Capitalism. The Case of The Industrial City of Łódź. Issue 2 (28th August 2014) - Marzec, Wiktor; Zysiak, Agata
Abstract: The article investigates the city of Łódź as an exceptional case of a settlement constitutive of different kinds and techniques of power typical of nineteenth century industrial capitalism. We consider Foucault's disciplinary power/biopower through the convergence of the paternalistic gaze of the factory owner, and the Tsarist rule in the Scheibler and Grohman industrial establishment and the nearby workers housing estate. The aim of this article is to investigate a specific locus of peripheral capitalism and the relations accompanying it through the Foucauldian analysis of power. We argue that unique and unstable patterns of correlation of power techniques emerged here. Power is no longer strictly related to the temporal matrix or the functional demands of capitalist production, and only temporarily ossified in contingent configurations. While Foucault's canonical theoretical premises and concepts are of explanatory value, the very relations between them become problematic when confronted with the particular entanglement in Łódź. Therefore we opt for the new paradigm of power analysis through S. J. Collier's "topological analysis".